An Analysis of Students’ Speaking Anxiety at the Eleventh Grade of Sman 11 Pandeglang in Academic Year 2024/2025 - Irfan Rois; Rizdki Elang Gumelar; Riandi (Jurnal Bahasa Inggris Terapan, 2025)
This study investigates the factors and types of speaking anxiety experienced by eleventh-grade students at SMAN 11 Pandeglang during the 2024/2025 academic year. Speaking anxiety is a common issue in foreign language learning that can negatively affect students’ performance, confidence, and motivation. The research focuses on four major factors contributing to speaking anxiety: low English proficiency, lack of familiarity with the task, low confidence, and fear of making mistakes. Before distributing the questionnaire, short interviews were conducted with two students one male and one female to gain initial insights into their feelings and difficulties when speaking English in class. These interviews ensured that the questionnaire items were clear, relevant, and contextually appropriate. The questionnaire, which aimed only to identify the types and factors of anxiety without influencing students’ emotions, was administered to 25 students. The results revealed that fear of making mistakes was the dominant factor (27.1%), followed by lack of familiarity with the task (25.9%), lack of confidence (24.6%), and low English proficiency (22.3%). Regarding the types of anxiety, trait anxiety was found to be slightly more prevalent (51.5%) than state anxiety (48.4%). Data were collected through questionnaires and classroom observations, providing a comprehensive understanding of students’ anxiety experiences. These findings emphasize the need for English teachers to foster a supportive and low-anxiety classroom environment by offering constructive feedback, designing familiar and engaging speaking tasks, and helping students build self-confidence in their language learning process.